Reactive epoxy fully-recycled asphalt mixture and use method thereof
By using reactive epoxy full regeneration technology in the regenerated asphalt mixture, chemical crosslinking with RAP material using fully regenerated epoxy resin and curing agent, the problems of insufficient performance and low durability of existing regenerated asphalt mixtures are solved, and the effect of efficient use of RAP material and reducing the amount of newly added asphalt is achieved.
Patent Information
- Application Number
- CN202411908518.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-25
AI Technical Summary
In use, existing regenerated asphalt mixtures have problems such as aggregate variability, difficulty in using aging asphalt, coarse aggregate oil film and fine aggregate oil groups, resulting in insufficient road performance, and traditional regenerating agents are prone to precipitation during service, resulting in insufficient durability performance.
Reactive epoxy fully regenerated asphalt mixture is used to improve the compatibility between the components by chemical cross-linking between the fully regenerated epoxy resin, the fully regenerated curing agent, the RAP crude material, the RAP fine material and the reactive asphalt, forming epoxy regenerated asphalt with a stable phase structure, and achieving firm bonding with the RAP material, reducing the amount of newly added asphalt, and making full use of the RAP material.
The bonding performance and durability of the recycled asphalt mixture has been greatly improved, the amount of newly added asphalt has been reduced, the full regeneration has been achieved, the road performance has been improved, and the problems analyzed by the lightweight group have been solved.
Smart Images

Figure CN119683907A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of road and bridge materials, and in particular to a reactive epoxy fully recycled asphalt mixture and a use method thereof. Background Art
[0002] Asphalt pavement construction in my country has gradually changed from an era of construction-oriented to an era of equal emphasis on construction and maintenance, during which a large amount of recycled asphalt mixtures have been produced. However, due to the wide source of recycled asphalt mixtures, large variability, and the presence of a large number of oil particles, the heating temperature of existing recycling equipment is also limited (usually 120°C to 130°C), the asphalt film coated on the surface of coarse RAP material is difficult to melt, and the oil particles composed of fine RAP material are difficult to open, resulting in difficulties in grading design. Therefore, most recycled asphalt mixtures are not used efficiently, usually with a low recycled material content (<30%) and are mostly used in cushion layers or low-grade roads.
[0003] The existing recycling technology mainly aims to restore the performance of aged asphalt to its original level. The addition of light components that are missing from aged asphalt has a certain recovery effect on aged asphalt, but it has not fundamentally solved the problems of aggregate variability, difficulty in utilizing aged asphalt, oil film of coarse aggregate and oil clusters of fine aggregate. In actual engineering, it is often necessary to add a large amount of new asphalt and new aggregate to adjust the gradation. However, there are still problems such as insufficient bonding performance of new asphalt with coarse RAP materials and fine RAP materials, and poor compatibility with aged asphalt, which leads to insufficient road performance of recycled asphalt mixture. In addition, traditional regeneration agents mainly composed of light components are easily precipitated during the service of recycled asphalt pavement, resulting in serious insufficient durability of the prepared recycled asphalt mixture.
[0004] The information disclosed in this background technology section is only intended to deepen the understanding of the overall background technology of the present invention, and should not be regarded as acknowledging or suggesting in any form that the information constitutes the prior art known to those skilled in the art. Summary of the invention
[0005] The first purpose of the present invention is to provide a reactive epoxy fully recycled asphalt mixture, which greatly improves the compatibility between the components through mutual chemical cross-linking among fully recycled epoxy resin, fully recycled curing agent, RAP coarse material, RAP fine material and reactive asphalt, forms epoxy recycled asphalt with a stable phase structure, and achieves strong bonding between it and RAP material, greatly reduces the amount of newly added asphalt, fully utilizes RAP material, and realizes full regeneration.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is: a reactive epoxy fully recycled asphalt mixture, the reactive epoxy fully recycled asphalt mixture is composed of fully recycled epoxy resin, fully recycled curing agent, RAP coarse material, RAP fine material and reactive asphalt;
[0007] Fully recycled epoxy resin, calculated by weight, includes the following components:
[0008] 40-50 parts of high molecular weight epoxy resin;
[0009] 5 to 15 parts of low molecular weight epoxy compound;
[0010] 5-10 parts of multifunctional biomass blending oil;
[0011] 0.1-0.3 parts of accelerator;
[0012] The fully recycled curing agent is calculated by weight and includes the following components:
[0013] 1 to 3 parts of medium temperature curing agent;
[0014] 5-10 parts of room temperature curing agent;
[0015] 0.1-0.3 parts dopamine;
[0016] Furthermore, the fully recycled epoxy resin is pre-mixed with the RAP fine material; the fully recycled curing agent is pre-mixed with the RAP coarse material. In the present invention, the mass ratio of the fully recycled epoxy resin, the fully recycled curing agent, the RAP coarse material, and the RAP fine material is 0.4-0.8: 0.2-0.4: 50-80: 20-50, wherein the epoxy resin system dosage is 0.6% to 1.2% of the sum of the RAP fine material and the RAP coarse material. The ratio of epoxy resin to curing agent is optimized to ensure that the epoxy reaction system can be fully cured to form high-strength, high-bonding active mortar and modified aggregate. An appropriate amount of epoxy resin and curing agent can make up for the insufficient bonding caused by aging asphalt in the RAP material, and improve the bonding performance and durability of the overall material.
[0017] Furthermore, RAP fines were depolymerized by microwave heating at 150-180°C for 0.5h to depolymerize into aged asphalt, fine aggregate and filler; the internal covalent bonds of the asphalt reacted to generate hydroxyl and carbonyl groups under the intrinsic driving mechanism of thermal oxidative aging, and aromatic compounds containing benzene rings and their derivatives were oxidized into carboxyl groups, and the active groups could undergo cross-linking reactions with epoxy groups under the action of promoters.
[0018] Furthermore, dopamine will slowly self-polymerize to form polydopamine under the weak alkaline conditions of the curing agent and the slight oxidation catalysis of oxygen. At this time, polydopamine is negatively charged in a weakly alkaline environment. When the fully recycled curing agent is mixed with RAP coarse aggregate, the aged asphalt film on the surface of the RAP coarse aggregate is acidic, causing the weakly alkaline environment to transform into a weakly acidic environment, and polydopamine is positively charged under weakly acidic conditions. Since the aged asphalt contains more negatively charged asphaltene, the positively charged polydopamine is firmly adhered to the surface of the RAP coarse aggregate under the synergistic effect of physical deposition and complexation reaction, giving the RAP coarse aggregate an amine group with higher reaction activity, so as to facilitate cross-linking reaction with the epoxy system, thereby enhancing the bonding performance of the RAP coarse aggregate with active mortar and reactive asphalt.
[0019] Furthermore, the multifunctional bio-based blending oil is prepared by modifying biomass blending oil through epoxidation and anhydride modification; biomass blending oil itself contains hydroxyl groups, so the multifunctional bio-based blending oil contains active reaction groups such as epoxy groups, anhydride groups and hydroxyl groups, and can simultaneously undergo cross-linking reactions with the epoxy system, RAP coarse material and reactive asphalt, increasing the compatibility while stably existing in the system under the restriction of the cross-linking network, solving the precipitation problem of lightweight components during service.
[0020] Further, the preparation process of the multifunctional bio-based blending oil is as follows:
[0021] S1. Mix and stir the bio-based blending oil, glacial acetic acid and sodium hydroxide in a water bath and heat to 30°C, then drop a formulated amount of hydrogen peroxide and complete the dropwise addition within 45 minutes. Keep the mixture at 30°C for 24 hours, then separate the reaction mixture into layers and perform vacuum distillation to obtain the epoxidized bio-based blending oil.
[0022] S2. Heat the epoxidized bio-based blending oil to 60° C. and add maleic anhydride. After the maleic anhydride is completely dissolved, add an esterification catalyst and continue the reaction for 1 hour to finally obtain a multifunctional bio-based blending oil.
[0023] Furthermore, biomass blended oil is obtained by physical treatment of bio-oil, the purpose of which is to remove moisture and residues from crude oil and further purify it.
[0024] Furthermore, the bio-oil includes one or more of date seed oil, peanut oil, and soybean oil. The bio-oil is rich in light components and has high permeability, which can reduce the relative content of asphaltene in aged asphalt, thereby adjusting the components of aged asphalt and restoring the performance of aged asphalt.
[0025] Furthermore, the viscosity of the multifunctional bio-based blending oil at 25°C is 5mPa·s to 10mPa·s, which is relatively low. It can be used as a diluent for epoxy resin to reduce the viscosity of epoxy resin, reduce mixing difficulty, and increase mixing uniformity.
[0026] Furthermore, the reactive asphalt is prepared from a reactive elastomer and a high-grade asphalt in a mass ratio of 1:19-20; the reactive elastomer is prepared from an epoxidized elastomer and an anhydride elastomer in a 1:1 ratio; the reactive elastomer is instantly soluble, swells and disperses rapidly in asphalt at high temperatures, and provides reaction sites to the asphalt, facilitating cross-linking reactions with the epoxy system and RAP coarse material, thereby improving the compatibility of the system; in addition, the elastomer network can further supplement the degraded polymer network in the aged modified asphalt, thereby improving the road performance of the epoxy fully recycled asphalt mixture.
[0027] Furthermore, the high-grade asphalt is one or more of 90# asphalt and 110# asphalt. The use of high-grade soft asphalt can further balance the high hardness and high viscosity of aged asphalt.
[0028] Furthermore, the accelerator is one or more of tertiary amines, quaternary ammonium salts and metal carboxylates. Preferably, the accelerator can effectively promote the crosslinking reaction between the epoxy group and the carbonyl group or the carboxyl group.
[0029] Furthermore, the high molecular weight epoxy resin is one or more of E51 and E44; the molecular weight of the high molecular weight epoxy resin ranges from 10,000 to 15,000, the molecular weight is large, the distance between epoxy groups is far, the reaction activity is low, and in the pre-mixing stage with the RAP fine material, it does not preferentially participate in the reaction, thereby ensuring the low cross-linking degree and fluidity of the active mortar.
[0030] Furthermore, the low molecular weight epoxy compound is one or more of C12-14 alkyl glycidyl ether, trimethylolpropane glycidyl ether and 4,4'-diaminodiphenylmethane tetraglycidylamine; the molecular weight range of the low molecular weight epoxy compound is 500-1000, the molecular weight is low, the distance between epoxy groups is small, the reaction activity is large, and it is easy to undergo cross-linking reaction with the active groups in the aged asphalt. On the one hand, it improves the compatibility of the epoxy resin with the aged asphalt, and on the other hand, it can form a solidified network with low cross-linking density through the reaction to stabilize the fine particles, thereby forming an active mortar with a stable phase structure.
[0031] Furthermore, there may also be a large amount of aged SBS modified asphalt in the aged asphalt. The SBS molecular chains break after aging, and hydroxyl and carboxyl groups are generated at the ends of the PB and PS segments, which can undergo cross-linking reactions with low molecular weight epoxy compounds, thereby repairing the broken SBS molecular chains and achieving synergistic modification of the SBS polymer network and the epoxy network, thereby improving the road performance of the epoxy fully recycled asphalt mixture.
[0032] Furthermore, the medium-temperature curing agent is one or more of meta-phenylenediamine and low molecular weight polyamide; the amine value range of the medium-temperature curing agent is 150-200 mgKOH / g; the purpose of the preferred amine value range is: greater than 150 mgKOH / g is to ensure a certain reaction activity, to ensure that a cross-linking reaction occurs with epoxy during medium-temperature processes such as mixing, transportation, paving, and rolling, so that the epoxy fully recycled asphalt mixture system has a certain viscosity, avoiding problems such as epoxy asphalt segregation and oil overflow during rolling; less than 200 mgKOH / g is to avoid excessive reaction activity resulting in excessive cross-linking density of the system, resulting in problems such as difficulty in rolling.
[0033] Furthermore, the room temperature curing agent is one or more of ethylenediamine, hexamethylenediamine, and diethylenetriamine; the amine value range of the room temperature curing agent is 400-600 mgKOH / g; the purpose of the preferred amine value range is: greater than 400 mgKOH / g is to ensure that the high reaction activity can quickly undergo cross-linking and curing reaction with the epoxy resin after the temperature is reduced to room temperature during the curing stage, quickly strengthen, and greatly reduce the curing time; less than 600 mgKOH / g is to avoid excessive reaction activity and runaway reaction at other temperatures.
[0034] Furthermore, the pH values of the medium temperature curing agent and the room temperature curing agent are both 8 to 8.5. The purpose of preferably using a weak alkaline curing agent is to provide a weak alkaline environment for dopamine that is conducive to its self-polymerization.
[0035] The second object of the present invention is to provide a reactive epoxy fully recycled asphalt mixture having the same technical effect.
[0036] In order to achieve the above object, the technical solution adopted by the present invention is: a method for using a reactive epoxy fully recycled asphalt mixture, comprising the following steps:
[0037] P1. Pre-separate RAP into RAP fine material and RAP coarse material by fine screening;
[0038] P2 and RAP fines are depolymerized by microwave heating and mixed with fully recycled epoxy resin to form active mortar;
[0039] P3, mixing RAP coarse material with fully recycled curing agent, performing surface modification, and forming active aggregate;
[0040] P4, adding reactive elastomer into high-grade asphalt to form reactive asphalt;
[0041] P5. Mix the active mortar, active aggregate and reactive asphalt in proportion to form epoxy fully recycled asphalt mixture.
[0042] Furthermore, a method for using a reactive epoxy fully recycled asphalt mixture is specifically as follows:
[0043] P1. RAP is divided into RAP fine material (0mm-8mm) and RAP coarse material (8mm-20mm) by fine screening with 8mm as the boundary. Coarse material above 20mm needs further crushing and screening;
[0044] Aggregate variability is reflected in the destruction of the original gradation after RAP material is crushed, showing that fine material is more and coarse material is less, and RAP material from different sources and with different original gradations cannot be used directly. The present invention screens RAP material into RAP coarse material and RAP fine material through fine screening, and then processes the RAP coarse material and RAP fine material respectively according to their different characteristics, thereby minimizing the influence of aggregate variability.
[0045] P2, RAP fine material is depolymerized into aged asphalt, fine aggregate and filler by microwave heating (150℃~180℃) for 0.5h.
[0046] Add fully recycled epoxy resin and continue stirring for 0.5h to form active mortar;
[0047] Both RAP fines and RAP coarse materials contain aged asphalt, the difference being that RAP fines contain more aged asphalt, which can be utilized, while RAP coarse materials contain less aged asphalt, which can be ignored. The present invention heats and depolymerizes RAP fines, which can eliminate the oil cluster phenomenon and obtain most of the aged asphalt in RAP fines, but the specific amount cannot be accurately determined because some of the aged asphalt enters the pores of the aggregate and is difficult to utilize, and the approximate range is 3.6% to 4.8% of the RAP material.
[0048] Furthermore, the microwave heating temperature is preferably 150° C. to 180° C., the purpose of which is to depolymerize RAP fines as much as possible and collect aged asphalt while preventing the aged asphalt from further carbonizing and losing its utilization value.
[0049] P3, mix and stir the RAP coarse material and the fully recycled curing agent at room temperature for 1 hour, and continue to stand for 1 hour after the reaction is completed to perform surface modification and form active aggregate;
[0050] The fully recycled curing agent reacts with the aged oil film on the surface of the coarse aggregate, removes the negative impact of the aged asphalt oil film, and improves the surface activity of the coarse aggregate. The surface-modified coarse aggregate can achieve better bonding with new asphalt, thereby enhancing the overall performance of the mixture.
[0051] P4. Add the reactive elastomer to the high-grade asphalt and stir at a high temperature of 165℃~180℃ for 0.5h, and continue swelling and developing for 1h to form reactive asphalt;
[0052] P5. Mix the active mortar, active aggregate and reactive asphalt in proportion at 120℃~130℃ for 75s~90s to form epoxy fully recycled asphalt mixture.
[0053] Furthermore, the mass ratio of the fully recycled epoxy resin, the fully recycled curing agent, the RAP coarse material, and the RAP fine material is 0.4-0.8: 0.2-0.4: 50-80: 20-50. The present invention is beneficial to the formation of the skeleton structure of the mixture and optimizes the overall mechanical properties by reasonably controlling the ratio of coarse and fine aggregates.
[0054] Furthermore, the amount of reactive asphalt needs to be further determined according to the source of RAP. For the upper layer RAP, it is added at 0.1% to 0.7% of the RAP mass ratio; for the upper and middle layer mixed RAP, it is added at 0.4% to 1.0% of the RAP mass ratio; for the upper, middle and lower layer mixed RAP, it is added at 0.7% to 1.3% of the RAP mass ratio. The amount of reactive asphalt added is 2.9% to 4.7% less than the amount of new asphalt required in ordinary recycled asphalt mixture (4.2% to 4.8%), which greatly reduces the amount of new asphalt added.
[0055] Beneficial Effects
[0056] (1) The present invention generates a network-stabilized fine material with a low degree of crosslinking by reacting fully recycled epoxy resin with aged asphalt in RAP fine material, and forms an active mortar; a fully recycled curing agent is pre-added to the RAP coarse material to modify its surface activity, and an active aggregate is formed; the active mortar, active aggregate and reactive asphalt are mixed, and the three components react with each other to greatly improve the compatibility. Finally, an epoxy recycled asphalt with a stable phase structure is formed, and a strong bond between it and the RAP material is achieved, which greatly reduces the amount of newly added asphalt, fully utilizes the RAP material, and achieves full regeneration.
[0057] (2) The preferred low molecular weight epoxy compound of the present invention has a small molecular distance and a high reactivity of the epoxy group. Under the action of the accelerator, it is easy to undergo a cross-linking reaction with the reactive groups such as carboxyl, hydroxyl and carbonyl in the aged asphalt. On the one hand, it improves the compatibility of epoxy resin with the aged asphalt. On the other hand, it can form a solidified network with a low cross-linking density through the reaction to stabilize the fine material and form an active mortar with a stable phase structure. In addition, the low molecular weight epoxy compound can also repair the molecular chain by reacting with the hydroxyl and carboxyl groups generated after the SBS molecular chain breaks, exerting the synergistic effect of the SBS elastomer network and the epoxy network, and improving the road performance of the epoxy fully recycled asphalt mixture.
[0058] (3) The preferred dopamine of the present invention will slowly self-polymerize to form polydopamine under the weak alkaline conditions provided by the curing agent and the slight oxidation catalysis of oxygen. Under the synergistic effect of physical deposition and complex reaction, polydopamine is firmly adhered to the surface of RAP coarse material, giving the RAP coarse material an amine group with higher reaction activity, so as to facilitate cross-linking reaction with the epoxy system, thereby enhancing the bonding performance of RAP coarse material with active mortar and reactive asphalt.
[0059] (4) The reactive asphalt provided by the present invention has multiple reaction sites, which facilitates cross-linking reaction with the epoxy system and RAP coarse material, thereby improving the compatibility of the system. In addition, the elastomer network can further supplement the degraded polymer network in the aged modified asphalt, thereby improving the road performance of the epoxy fully recycled asphalt mixture.
[0060] (5) The multifunctional biomass blending oil in the fully recycled epoxy resin provided by the present invention is rich in active groups and can undergo cross-linking reactions with the epoxy system, RAP coarse material and reactive asphalt at the same time. While increasing compatibility, it can stably exist in the system under the restriction of the cross-linking network, solving the problem of precipitation of light components during service. In addition, biomass oil is rich in light components and has high permeability, which can adjust the light components missing from aged asphalt and restore the performance of aged asphalt.
[0061] (6) The present invention pre-heats the RAP fine material by microwave heating (150°C to 180°C) to evenly and thoroughly break up the oil agglomerates in the RAP fine material, collects and utilizes aged asphalt as much as possible, and substantially reduces the amount of new asphalt while ensuring the road performance of the epoxy fully recycled asphalt mixture. In addition, the RAP coarse material with an asphalt film firmly attached to the surface is pre-activated to improve its compatibility and adhesion with epoxy asphalt, thereby making it a firm skeleton structure in the epoxy fully recycled asphalt mixture system. BRIEF DESCRIPTION OF THE DRAWINGS
[0062] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the prior art descriptions will be briefly introduced below. Obviously, the drawings described below are only some embodiments in the records of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0063] Figure 1 The present invention is a flow chart of the use method of reactive epoxy fully recycled asphalt mixture. DETAILED DESCRIPTION
[0064] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined purpose of the invention, a reactive epoxy fully recycled asphalt mixture provided by the present invention, its specific implementation method, characteristics and effects are described in detail as follows.
[0065] Sources of raw materials used in the examples:
[0066] High molecular weight epoxy resin: E51, E44, 1688 Alibaba procurement and wholesale network.
[0067] Low molecular weight epoxy compounds: C12-14 alkyl glycidyl ether, trimethylolpropane glycidyl ether and 4,4'-diaminodiphenylmethane tetraglycidylamine, 1688 Alibaba procurement wholesale network.
[0068] Bio-oil: date seed oil, peanut oil, soybean oil, 1688 Alibaba procurement and wholesale network.
[0069] Accelerator: 2,4,6-tris(dimethylaminomethyl)phenol, quaternary ammonium salt, zinc cyclohexaneate, 1688 Alibaba procurement and wholesale network.
[0070] Medium temperature curing agent: meta-phenylenediamine, low molecular weight polyamide, 1688 Alibaba procurement and wholesale network.
[0071] Room temperature curing agent: ethylenediamine, hexamethylenediamine, diethylenetriamine, 1688 Alibaba procurement and wholesale network.
[0072] Dopamine, 1688 Alibaba procurement and wholesale network.
[0073] Epoxidized elastomer: Epoxidized SBS, 1688 Alibaba procurement wholesale network.
[0074] Anhydride elastomer: EVA-g-MAH, SEBS-g-MAH, 1688 Alibaba procurement and wholesale network.
[0075] High-grade asphalt: 90# base asphalt, 110# base asphalt, Sinopec Baling Petrochemical Co., Ltd.
[0076] Conventional chemical reagents and materials involved: sodium hydroxide, glacial acetic acid, 30% hydrogen peroxide, 98% concentrated sulfuric acid, maleic anhydride, esterification catalyst, Shanghai Aladdin Biochemical Technology Co., Ltd.
[0077] The preparation method of the multifunctional bio-based blending oil in the embodiments and comparative examples is:
[0078] S1. Mix 100 mL of bio-based blending oil, 3 mL of glacial acetic acid, and 2 g of sodium hydroxide, stir and place in a water bath, heat to 30°C, add 30 mL of hydrogen peroxide dropwise, and complete the addition within 45 min. Keep the mixture at 30°C for 24 h, then separate the reaction mixture into layers, and distill under reduced pressure to obtain epoxidized bio-based blending oil;
[0079] S2. Heat the epoxidized bio-based blending oil to 60°C, add 20 g of maleic anhydride, and after the maleic anhydride is completely dissolved, add 0.3 mL of esterification catalyst and continue the reaction for 1 hour to finally obtain a multifunctional bio-based blending oil.
[0080] The preparation methods of the mixtures in the examples and comparative examples refer to the "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering" (JTG E20-2011).
[0081] Example 1
[0082] The reactive epoxy fully recycled asphalt mixture provided in this embodiment is calculated by weight, and the selected fully recycled epoxy resin includes 40 parts of E51, 5 parts of C12-14 glycidyl ether, 5 parts of multifunctional biomass blending oil, and 0.1 part of 2,4,6-tris(dimethylaminomethyl)phenol; the selected fully recycled curing agent includes 1 part of m-phenylenediamine, 5 parts of ethylenediamine, and 0.1 part of dopamine.
[0083] A method for using a reactive epoxy fully recycled asphalt mixture is specifically as follows:
[0084] P1. RAP is divided into RAP fine material (0mm-8mm) and RAP coarse material (8mm-20mm) by fine screening with 8mm as the boundary. Coarse material above 20mm needs further crushing and screening;
[0085] P2 and RAP fine materials were depolymerized into aged asphalt, fine aggregate and filler by microwave heating (150°C to 180°C), and fully recycled epoxy resin was added and stirred for 0.5h to form active mortar;
[0086] P3, mix and stir the RAP coarse material and the fully recycled curing agent at room temperature for 1 hour, and continue to stand for 1 hour after the reaction is completed to perform surface modification and form active aggregate;
[0087] P4. Add the reactive elastomer to the high-grade asphalt and stir at a high temperature of 165℃~180℃ for 0.5h, and continue swelling and developing for 1h to form reactive asphalt;
[0088] P5. Mix the active mortar, active aggregate and reactive asphalt for 75s to 90s to form an epoxy fully recycled asphalt mixture, wherein the epoxy resin system is added in an amount of 0.6% of the RAP material and the reactive asphalt is added in an amount of 0.4% of the RAP material.
[0089] The performance test results of Example 1 are as follows:
[0090] Table 1 Test results of reactive epoxy fully recycled asphalt mixture in Example 1
[0091]
[0092]
[0093] Note: 1- Long-term service is simulated by placing in a UV heat aging box for 30 days.
[0094] Example 2
[0095] The reactive epoxy fully recycled asphalt mixture provided in this embodiment is calculated by weight, and the selected fully recycled epoxy resin includes 45 parts of E51, 10 parts of trimethylolpropane glycidyl ether, 7 parts of multifunctional biomass blending oil, and 0.2 parts of quaternary ammonium salt; the selected fully recycled curing agent includes 2 parts of low molecular weight polyamide, 7 parts of hexamethylenediamine, and 0.2 parts of dopamine.
[0096] A method for using a reactive epoxy fully recycled asphalt mixture is specifically as follows:
[0097] P1. RAP is divided into RAP fine material (0mm-8mm) and RAP coarse material (8mm-20mm) by fine screening with 8mm as the boundary. Coarse material above 20mm needs further crushing and screening;
[0098] P2 and RAP fine materials were depolymerized into aged asphalt, fine aggregate and filler by microwave heating (150°C to 180°C), and fully recycled epoxy resin was added and stirred for 0.5h to form active mortar;
[0099] P3, mix and stir the RAP coarse material and the fully recycled curing agent at room temperature for 1 hour, and continue to stand for 1 hour after the reaction is completed to perform surface modification and form active aggregate;
[0100] P4. Add the reactive elastomer to the high-grade asphalt and stir at a high temperature of 165℃~180℃ for 0.5h, and continue swelling and developing for 1h to form reactive asphalt;
[0101] P5. Mix the active mortar, active aggregate and reactive asphalt for 75s to 90s to form an epoxy fully recycled asphalt mixture, wherein the epoxy resin system is added in an amount of 0.9% of the RAP material and the reactive asphalt is added in an amount of 0.7% of the RAP material.
[0102] The performance test results of Example 2 are as follows:
[0103] Table 2 Test results of reactive epoxy fully recycled asphalt mixture in Example 2
[0104] Experimental Project unit Test results Test methods Marshall stability (60℃) kN 22.41 JTG E20 T0709 Marshall specimen void ratio % 2.2 JTG E20 T0709 Freeze-thaw splitting test strength ratio % 95.4 JTG E20 T0729 Dynamic stability (70℃, 0.7MPa) Times / mm 16479 JTG E20 T0719 Maximum bending failure strain (-10℃) <![CDATA[10 -6 ]]> 2537 JTG E20 T0715 Maximum bending failure strain after simulating long-term service (-10℃) <![CDATA[10 -6 ]]> 2487 JTG E20 T0715
[0105] Note: 1- Long-term service is simulated by placing in a UV heat aging box for 30 days.
[0106] Example 3
[0107] The reactive epoxy fully recycled asphalt mixture provided in this embodiment is calculated by weight, and the selected fully recycled epoxy resin includes 50 parts of E44, 15 parts of 4,4'-diaminodiphenylmethane tetraglycidylamine, 10 parts of multifunctional biomass blending oil, and 0.3 parts of zinc cyclohexane; the selected fully recycled curing agent includes 3 parts of meta-phenylenediamine, 10 parts of diethylenetriamine, and 0.3 parts of dopamine.
[0108] A method for using a reactive epoxy fully recycled asphalt mixture is specifically as follows:
[0109] P1. RAP is divided into RAP fine material (0mm-8mm) and RAP coarse material (8mm-20mm) by fine screening with 8mm as the boundary. Coarse material above 20mm needs further crushing and screening;
[0110] P2 and RAP fine materials were depolymerized into aged asphalt, fine aggregate and filler by microwave heating (150°C to 180°C), and fully recycled epoxy resin was added and stirred for 0.5h to form active mortar;
[0111] P3, mix and stir the RAP coarse material and the fully recycled curing agent at room temperature for 1 hour, and continue to stand for 1 hour after the reaction is completed to perform surface modification and form active aggregate;
[0112] P4. Add the reactive elastomer to the high-grade asphalt and stir at a high temperature of 165℃~180℃ for 0.5h, and continue swelling and developing for 1h to form reactive asphalt;
[0113] P5. Mix the active mortar, active aggregate and reactive asphalt for 75s to 90s to form an epoxy fully recycled asphalt mixture, wherein the epoxy resin system is added in an amount of 1.2% of the RAP material and the reactive asphalt is added in an amount of 1.0% of the RAP material.
[0114] The performance test results of Example 3 are as follows:
[0115] Table 3 Test results of reactive epoxy fully recycled asphalt mixture in Example 3
[0116] Experimental Project unit Test results Test methods Marshall stability (60℃) kN 23.57 JTG E20 T0709 Marshall specimen void ratio % 1.9 JTG E20 T0709 Freeze-thaw splitting test strength ratio % 98.2 JTG E20 T0729 Dynamic stability (70℃, 0.7MPa) Times / mm 14367 JTG E20 T0719 Maximum bending failure strain (-10℃) <![CDATA[10 -6 ]]> 2763 JTG E20 T0715 Maximum bending failure strain after simulating long-term service (-10℃) <![CDATA[10 -6 ]]> 2675 JTG E20 T0715
[0117] Note: 1- Long-term service is simulated by placing in a UV heat aging box for 30 days.
[0118] Comparative Example 1
[0119] The fully recycled epoxy resin and fully recycled curing agent used in this comparative example are the same as those in Example 2.
[0120] The method for using the reactive epoxy fully recycled asphalt mixture provided in this comparative example is different from that in Example 2 in that: P2 and P3 are not performed, and the fully recycled epoxy resin, the fully recycled curing agent, the reactive asphalt, the RAP fine material and the RAP coarse material are directly mixed simultaneously. The remaining steps are the same as in Example 2.
[0121] The performance test results of Comparative Example 1 are as follows:
[0122] Table 4 Test results of reactive epoxy fully recycled asphalt mixture in comparative example 1
[0123] Experimental Project unit Test results Test methods Marshall stability (60℃) kN 13.25 JTG E20 T0709 Marshall specimen void ratio % 5.8 JTG E20 T0709 Freeze-thaw splitting test strength ratio % 75.3 JTG E20 T0729 Dynamic stability (70℃, 0.7MPa) Times / mm 9143 JTG E20 T0719 Maximum bending failure strain (-10℃) <![CDATA[10 -6 ]]> 1648 JTG E20 T0715 Maximum bending failure strain after simulating long-term service (-10℃) <![CDATA[10 -6 ]]> 1542 JTG E20 T0715
[0124] Note: 1- Long-term service is simulated by placing in a UV heat aging box for 30 days.
[0125] As shown in Table 4, compared with Example 2, Comparative Example 1 directly mixes all components, lacks the steps of pre-depolymerization of RAP fine material and pre-activation modification of RAP coarse material, resulting in uncontrollable chemical reaction priority and reaction degree between the components, and unable to form active mortar and active aggregate, and the chemical bonding between the components is weakened, resulting in compatibility attenuation, bonding performance attenuation and a small oil-stone ratio. Finally, the strength, high and low temperature performance, and water damage resistance of the mixture are greatly reduced, and the void ratio also increases sharply.
[0126] Comparative Example 2
[0127] The fully recycled epoxy resin and fully recycled curing agent used in this comparative example are the same as those in Example 2.
[0128] The method for using the reactive epoxy fully recycled asphalt mixture provided in this comparative example is different from that in Example 2, the fully recycled epoxy resin is directly mixed and stirred with the RAP fine material in P2, and the RAP fine material is not pre-heated with microwaves. The remaining steps are the same as in Example 2.
[0129] The performance test results of Comparative Example 2 are as follows:
[0130] Table 5 Test results of reactive epoxy fully recycled asphalt mixture in comparative example 2
[0131] Experimental Project unit Test results Test methods Marshall stability (60℃) kN 17.65 JTG E20 T0709 Marshall specimen void ratio % 5.4 JTG E20 T0709 Freeze-thaw splitting test strength ratio % 80.3 JTG E20 T0729 Dynamic stability (70℃, 0.7MPa) Times / mm 10476 JTG E20 T0719 Maximum bending failure strain (-10℃) <![CDATA[10 -6 ]]> 1823 JTG E20 T0715 Maximum bending failure strain after simulating long-term service (-10℃) <![CDATA[10 -6 ]]> 1759 JTG E20 T0715
[0132] Note: 1- Long-term service is simulated by placing in a UV heat aging box for 30 days.
[0133] As shown in Table 5, compared with Example 2, the RAP fines in Comparative Example 2 were not pre-treated with microwave heating, and the oil mass particles were not depolymerized, resulting in structural weaknesses in the epoxy fully recycled asphalt mixture, which led to a significant reduction in the strength of the mixture. At the same time, a large amount of aged asphalt was not utilized, and the initial cross-linking network of aged asphalt and fully recycled epoxy resin was lacking, and the mortar system was also difficult to maintain phase stability, resulting in a simultaneous decrease in high and low temperature performance. In addition, the lack of aged asphalt will also result in a small oil-stone ratio, resulting in a sharp increase in porosity.
[0134] Comparative Example 3
[0135] The fully recycled epoxy resin used in this comparative example is the same as that in Example 2; the fully recycled curing agent used is different from that in Example 2 except that no dopamine is added; the other components are the same as those in Example 2.
[0136] The method for using the reactive epoxy fully recycled asphalt mixture provided in this comparative example is different from that in Example 2 in that: in P3, the fully recycled curing agent is directly mixed with the RAP coarse material without undergoing activation treatment. The remaining steps are the same as in Example 2.
[0137] The performance test results of Comparative Example 3 are as follows:
[0138] Table 6 Test results of reactive epoxy fully recycled asphalt mixture in comparative example 3
[0139] Experimental Project unit Test results Test methods Marshall stability (60℃) kN 15.37 JTG E20 T0709 Marshall specimen void ratio % 2.4 JTG E20 T0709 Freeze-thaw splitting test strength ratio % 85.6 JTG E20 T0729 Dynamic stability (70℃, 0.7MPa) Times / mm 9785 JTG E20 T0719 Maximum bending failure strain (-10℃) <![CDATA[10 -6 ]]> 1978 JTG E20 T0715 Maximum bending failure strain after simulating long-term service (-10℃) <![CDATA[10 -6 ]]> 1902 JTG E20 T0715
[0140] Note: 1- Long-term service is simulated by placing in a UV heat aging box for 30 days.
[0141] As shown in Table 6, compared with Example 2, Comparative Example 3 did not perform activation modification on the RAP coarse aggregate, resulting in a lack of chemical bonding between the RAP coarse aggregate and the active mortar and reactive asphalt, resulting in insufficient bonding performance between the RAP coarse aggregate and the binder, making it difficult to become a strong skeleton support point for the epoxy fully recycled asphalt mixture, ultimately resulting in a significant reduction in the strength, high and low temperature performance and water damage resistance of the mixture.
[0142] Comparative Example 4
[0143] The fully recycled epoxy resin and fully recycled curing agent used in this comparative example are the same as those in Example 2.
[0144] The method for using the reactive epoxy fully recycled asphalt mixture provided in this comparative example is different from that in Example 2 in that: in P4, no reactive elastomer is used to modify the high-grade asphalt. The remaining steps are the same as in Example 2.
[0145] The performance test results of Comparative Example 4 are as follows:
[0146] Table 7 Test results of reactive epoxy fully recycled asphalt mixture in comparative example 4
[0147] Experimental Project unit Test results Test methods Marshall stability (60℃) kN 18.75 JTG E20 T0709 Marshall specimen void ratio % 2.3 JTG E20 T0709 Freeze-thaw splitting test strength ratio % 88.74 JTG E20 T0729 Dynamic stability (70℃, 0.7MPa) Times / mm 11345 JTG E20 T0719 Maximum bending failure strain (-10℃) <![CDATA[10 -6 ]]> 2013 JTG E20 T0715 Maximum bending failure strain after simulating long-term service (-10℃) <![CDATA[10 -6 ]]> 1941 JTG E20 T0715
[0148] Note: 1- Long-term service is simulated by placing in a UV heat aging box for 30 days.
[0149] As shown in Table 7, compared with Example 2, Comparative Example 4 did not use reactive elastomer to modify the high-grade asphalt, resulting in the inability of the newly added asphalt to produce a cross-linking reaction with the aged asphalt, the epoxy system and the RAP coarse material, resulting in poor compatibility between the new and old asphalts, between the new asphalt and the epoxy system, and between the new asphalt and the RAP coarse material, thereby causing a significant decrease in the strength of the mixture, high and low temperature performance, and water damage resistance.
[0150] Comparative Example 5
[0151] The fully recycled epoxy resin used in this comparative example is different from that in Example 2 in that soybean oil is used instead of multifunctional bio-based blending oil; the fully recycled curing agent used is the same as that in Example 2.
[0152] The method of using the reactive epoxy fully recycled asphalt mixture provided in this comparative example is the same as that in Example 2.
[0153] The performance test results of Comparative Example 5 are as follows:
[0154] Table 8 Test results of reactive epoxy fully recycled asphalt mixture in comparative example 5
[0155] Experimental Project unit Test results Test methods Marshall stability (60℃) kN 20.33 JTG E20 T0709 Marshall specimen void ratio % 2.3 JTG E20 T0709 Freeze-thaw splitting test strength ratio % 89.6 JTG E20 T0729 Dynamic stability (70℃, 0.7MPa) Times / mm 15987 JTG E20 T0719 Maximum bending failure strain (-10℃) <![CDATA[10 -6 ]]> 2502 JTG E20 T0715 Maximum bending failure strain after simulating long-term service (-10℃) <![CDATA[10 -6 ]]> 1936 JTG E20 T0715
[0156] Note: 1- Long-term service is simulated by placing in a UV heat aging box for 30 days.
[0157] As shown in Table 7, compared with Example 2, Comparative Example 5 did not use multifunctional bio-based blending oil, but used soybean oil instead, which still had a certain recovery effect on the aged asphalt, so the maximum bending failure strain of the low-temperature beam did not significantly decay. However, due to the lack of cross-linking reaction between the multifunctional group and the epoxy system, the soybean oil precipitated from the epoxy fully recycled asphalt mixture system in the environment simulated for long-term service, resulting in a significant decay in the maximum bending failure strain of the low-temperature beam after the simulated long-term service.
[0158] Comparative Example 6
[0159] The fully recycled epoxy resin used in this comparative example is compared with that in Example 2, except that the low molecular weight epoxy compound is replaced by an equal amount of high molecular weight epoxy resin; the fully recycled curing agent used is the same as that in Example 2.
[0160] The method of using the reactive epoxy fully recycled asphalt mixture provided in this comparative example is the same as that in Example 2.
[0161] The performance test results of Comparative Example 6 are as follows:
[0162] Table 9 Test results of reactive epoxy fully recycled asphalt mixture in comparative example 6
[0163]
[0164]
[0165] Note: 1- Long-term service is simulated by placing in a UV heat aging box for 30 days.
[0166] As shown in Table 7, compared with Example 2, Comparative Example 6 does not use low molecular weight epoxy compounds, but instead uses all high molecular weight epoxy resins, which have low reactivity and a correspondingly reduced degree of reaction with active groups in aged asphalt, resulting in difficulty in forming an initial low cross-link density epoxy network, which makes it difficult to stabilize fine materials, and the broken SBS molecular chains in the aged asphalt cannot be repaired, ultimately resulting in a significant decrease in the strength and high and low temperature performance of the mixture.
[0167] Comparative Example 7
[0168] The fully recycled epoxy resin used in this comparative example is different from that in Example 2 in that no accelerator is added; the fully recycled curing agent used is the same as that in Example 2.
[0169] The method of using the reactive epoxy fully recycled asphalt mixture provided in this comparative example is the same as that in Example 2.
[0170] The performance test results of Comparative Example 7 are as follows:
[0171] Table 10 Test results of reactive epoxy fully recycled asphalt mixture in comparative example 7
[0172] Experimental Project unit Test results Test methods Marshall stability (60℃) kN 18.98 JTG E20 T0709 Marshall specimen void ratio % 2.5 JTG E20 T0709 Freeze-thaw splitting test strength ratio % 86.9 JTG E20 T0729 Dynamic stability (70℃, 0.7MPa) Times / mm 10275 JTG E20 T0719 Maximum bending failure strain (-10℃) <![CDATA[10 -6 ]]> 2006 JTG E20 T0715 Maximum bending failure strain after simulating long-term service (-10℃) <![CDATA[10 -6 ]]> 1975 JTG E20 T0715
[0173] Note: 1- Long-term service is simulated by placing in a UV heat aging box for 30 days.
[0174] As shown in Table 10, compared with Example 2, Comparative Example 7 did not add a promoter, resulting in insufficient cross-linking network density formed by the reaction of low molecular weight epoxy resin and aged asphalt, which made it difficult to stabilize the fine material and the broken SBS molecular chains in the aged asphalt could not be repaired, ultimately resulting in a significant decrease in the strength and high and low temperature performance of the mixture.
[0175] Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A reactive epoxy fully recycled asphalt mixture, characterized in that: The reactive epoxy fully recycled asphalt mixture is composed of fully recycled epoxy resin, fully recycled curing agent, RAP coarse material, RAP fine material and reactive asphalt; the fully recycled epoxy resin is pre-mixed with the RAP fine material; the fully recycled curing agent is pre-mixed with the RAP coarse material; The fully recycled epoxy resin comprises the following components, calculated by weight: 40~50 parts of high molecular weight epoxy resin; 5-15 parts of low molecular weight epoxy compound; 5-10 parts of multifunctional biomass blending oil; 0.1~0.3 parts of accelerator; The fully recycled curing agent comprises the following components, calculated by weight: 1~3 parts of medium temperature curing agent; 5~10 parts of room temperature curing agent; 0.1~0.3 parts of dopamine.
2. The reactive epoxy fully recycled asphalt mixture according to claim 1, characterized in that: The RAP fine material is depolymerized into aged asphalt, fine aggregate and filler; the aged asphalt can undergo a cross-linking reaction with epoxy groups under the action of an accelerator.
3. The reactive epoxy fully recycled asphalt mixture according to claim 1, characterized in that: The dopamine undergoes self-polymerization under aerobic weak alkaline conditions and adheres to the surface of the RAP coarse material under the synergistic effect of physical deposition and complexation reaction.
4. The reactive epoxy fully recycled asphalt mixture according to claim 1, characterized in that: The multifunctional bio-based blending oil is obtained by modifying the biomass blending oil through epoxidation and anhydride modification.
5. The reactive epoxy fully recycled asphalt mixture according to claim 1, characterized in that: The reactive asphalt is prepared from a reactive elastomer and a high-grade asphalt; the reactive elastomer is prepared by mixing an epoxidized elastomer and an anhydride elastomer in a mass ratio of 1:1; the high-grade asphalt is one or more of 90# asphalt and 110# asphalt.
6. The reactive epoxy fully recycled asphalt mixture according to claim 1, characterized in that: The accelerator is one or more of tertiary amines, quaternary ammonium salts and metal carboxylates.
7. The reactive epoxy fully recycled asphalt mixture according to claim 1, characterized in that: The high molecular weight epoxy resin is one or more of E51 and E44; the molecular weight range of the high molecular weight epoxy resin is 10000-15000; the low molecular weight epoxy compound is one or more of C12-14 alkyl glycidyl ether, trimethylolpropane glycidyl ether and 4,4'-diaminodiphenylmethane tetraglycidylamine; the molecular weight range of the low molecular weight epoxy compound is 500-1000.
8. The reactive epoxy fully recycled asphalt mixture according to claim 1, characterized in that: The medium-temperature curing agent is one or more of meta-phenylenediamine and low-molecular polyamide; the amine value range of the medium-temperature curing agent is 150-200 mgKOH / g; the room-temperature curing agent is one or more of ethylenediamine, hexamethylenediamine, and diethylenetriamine; the amine value range of the room-temperature curing agent is 400-600 mgKOH / g; the pH values of the medium-temperature curing agent and the room-temperature curing agent are both 8-8.
5.
9. The method for using a reactive epoxy fully regenerated asphalt mixture according to claims 1 to 8, characterized in that: The following steps are involved: P1. Pre-separate the recycled material into RAP fine material and RAP coarse material through fine screening; P2, depolymerizing the RAP fines by microwave heating and mixing with fully recycled epoxy resin to form an active mortar; P3, mixing RAP coarse material with fully recycled curing agent, performing surface modification, and forming active aggregate; P4, adding reactive elastomer into high-grade asphalt to form reactive asphalt; P5. Mix the active mortar, active aggregate and reactive asphalt in proportion to form a reactive epoxy fully recycled asphalt mixture.
10. The method for using a reactive epoxy fully recycled asphalt mixture according to claim 9, characterized in that: The microwave heating temperature in P2 is 150°C to 180°C.